Historical seismicity of the province of Chimborazo - Barahona Rivadeneira, Diego Javier; Barahona Ribadeneira , Wilson Roberto (Arandu UTIC, 2025)
This study analyzes the impact of gamification as a methodological strategy in the teaching of mathematics at the Basic General Education level. The research is based on the need to transform traditional pedagogical practices through innovative approaches that promote meaningful learning and the development of logical-mathematical skills. A qualitative approach with a descriptive design was used, applying interviews and direct observation with teachers and students from an educational institution in Ecuador. The results show that gamification enhances student motivation, engagement, and active participation in the classroom. Additionally, improvements were observed in the understanding of mathematical concepts, problem-solving, and collaborative work. It is concluded that integrating playful elements into teaching activities strengthens the teaching-learning process and contributes to a more dynamic, inclusive, and student-centered education. The study recommends training teachers in the use of digital tools and gamification strategies, as well as promoting educational policies that support active methodologies within the school curriculum.